Protocol for a scoping review of measures and definitions of gender-based discrimination linked to health outcomes in low and middle-income countries - Petitfour, Laurène; Srivastava, Swati; Shah-Rohlfs, Rupal; Orduhan, Clara; Quentin, Wilm; De Allegri, Manuela (BMJ open, 2022)
Introduction Gender-based discrimination (GBD) is generally defined as unequal or disadvantageous treatment based on one’s gender. Emerging evidence suggests that exposure to GBD in its various forms can yield negative consequences for women’s health, including delaying access to healthcare services and lowering the quality of nutrition. Although consensus exists around the theoretical definitions of GBD, current studies are limited on how to measure GBD empirically in order to assess its true impact on women’s health. Our mixed-methods scoping review aims at synthesising existing evidence by answering the question How is gender-based discrimination defined and measured in the health literature, with specific reference to Low and Middle-Income Countries (LMICs)?. Our ambition is to identify commonalities across definitions and measures to generate a dialogue towards reaching consensus around the development of a single standardised tool to be applied in health studies. - Methods and analysis Our mixed-method scoping review includes quantitative, qualitative and mixed-methods studies and unfolds according to the six stages proposed by Levac et al. Eligibility criteria for studies were defined in order to reflect the three core elements of the search, namely (1) the discrimination based on the gender, (2) the link to health outcomes and (3) the developing countries context. Four databases (PubMed, Web of Science, Cinahl and Econlit) were searched. We will extract and synthesise information from quantitative and qualitative studies following the framework proposed by Hong and use the Preferred Reporting Items for Systematic Reviews and Meta-analyses extension for scoping review tool as a guide. - Ethics and dissemination Since our scoping review relies exclusively on information extracted from published articles, its conduct is not subjected to ethical clearance. Results will be described and discussed in a peer-reviewed article and presented at relevant workshops and conferences.
Gesehen am 01.02.2023